Developing Learner Autonomy: Moroccan University EFL Teachers’ Perceived Views and Practices - OUSSOU, Said; ELBOUZIANY, Abdelhak; BOUALI, Hajare (Research and Innovation in Applied Linguistics, 2025)
Learner autonomy, or the ability to take control of one’s learning, has been in emergence for decades, and its importance has been widely acknowledged. However, there remains obscurity as to what teachers think about this concept and whether or not they are willing to promote it. Accordingly, this paper aimed to investigate 21 university professors’ views regarding their understanding of learner autonomy and the principles underlying it. The study used a mixed-method approach to provide rigorous analysis of the professors’ responses. Data were collected through a questionnaire after which ten professors were invited for a semi-structured interview to allow for more explanations of the views analyzed, thus adhering to the explanatory sequential design. Findings demonstrated that professors showed an understanding of the basic characteristics of learner autonomy. While each of the four orientations were maintained, the most supported was the technical orientation followed by the psychological orientation, a finding that was corroborated by the qualitative analysis wherein notions such as ‘motivation’, ‘metacognitive strategies’, and ‘decisions’ recurred. It was observed that their views were far less socially driven. This study has various implications for both theory and practice, particularly for EFL teachers both in this context and in other similar contexts.